Microlearning Videos for Green Knowledge Development: Feasibility, Learning Changes, and Cross-Case Patterns in Indonesian Vocational Education - Handayani, Mustika Nuramalia; Najib Tuisina Naenum; Nadia Trianisawati (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to describe the characteristics and assess the feasibility of videos used in Indonesia’s Agribusiness Processing of Agricultural Products (APHP) program, examine changes in students’ green knowledge within each case, and identify common and contrasting patterns of green-knowledge development across the two cases. A quantitative descriptive approach with comparative multiple-case secondary analysis was used. Both cases followed the ADDIE model but differed in content, participants, instructional models, implementation periods, and assessment instruments. Product feasibility was assessed through expert validation and student-response questionnaires. Cognitive outcomes were measured using multiple-choice pretests and posttests completed by 31 students in Case 1 and 25 students in Case 2. Six experts reviewed the mapping of the test items to six common green-knowledge domains. In Case 1, expert-validation scores ranged from 83.33% to 86.11%, and student practicality was 79.41%; in Case 2, expert-validation scores ranged from 75.00% to 95.14%, and student practicality was 83.98%. Green-knowledge scores increased from 32.26% to 68.87% in Case 1 and from 69.20% to 82.40% in Case 2, producing moderate normalized gains of 0.54 and 0.43. These results do not show that one instructional combination was superior. Instead, they illustrate two context-specific uses of microlearning: discovery activities for exploring broad environmental issues and project work for connecting sustainability with processing operations. By placing different topic-based tests within one framework, this study provides a practical basis for examining green knowledge across vocational food-processing subjects.